THREE ESSAYS ON BANK LENDING AND CORPORATE FINANCE - Chen, Liqiang (My University, 2013)
This thesis includes three essays on several important topics in empirical finance: Chief Executive Officer (CEO) risk-taking incentives, the cost and syndicate structure of bank loans and corporate investments with internal funds. This thesis contributes to these aspects of finance literature and the three essays are presented in Chapter 2, 3 and 4.
The first essay investigates how implicit contractual relationship between creditors and borrowers attenuates the conflict of interest between creditors and shareholders that arises from CEO compensation contracts when a corporation can be considered a nexus of explicit and implicit contractual relationships among stakeholders. We find that bank loans for firms with CEOs who are provided with risk-taking incentives have higher spreads and shorter maturities. A relationship between the lender and its borrower mitigates the influence of incentives for CEO risk-taking on loan spread and loan maturity. Such a relationship is especially beneficial for informationally opaque firms. The results are robust to the endogeneity of relationships and the simultaneous determination of loan spread, loan maturity and collateral requirements. Our results highlight the importance of the interaction between explicit and implicit contractual relationships to a firm’s borrowing cost.
The second essay investigates the effects of a borrowing firm’s CEO risk-taking incentives on the structure of the firm’s syndicated loans. The conflict of interest between creditors and shareholders arising from CEO risk-taking incentives is a major concern of borrower moral hazard for syndicate lenders, which require intensive monitoring by lead arrangers in a syndicate. When CEO risk-taking incentives are high, syndicates are structured to facilitate better due diligence and monitoring efforts. These syndicates have a smaller number of total lenders and are more concentrated, and lead arrangers will retain a greater portion of the loan. Moreover, we examine the factors that affect the link between CEO risk-taking incentives and syndicate loan structure. CEO risk-taking incentives have a lesser effect on the syndicate structure when lead arrangers have a good reputation and have a prior lending relationship with a borrowing firm. By contrast, CEO risk-taking incentives have a greater influence on syndicate structure when borrowing firms are informationally opaque, are financially distressed or have low growth prospects.
The third essay studies corporate investments with internal funds when firms face real investment friction using a sample of U.S. oil companies from 2003 to 2011 before and after the 2008 financial crisis. We show that firms’ capital expenditures are more sensitive to their lagged cash holdings than to their contemporaneous cash flows. By making investments with realized cash holdings, firms can avoid the investment adjustment costs that are incurred when investing with uncertain cash flows. We also show that cash flow policies are affected by liquidity constraints following the 2008 financial crisis: firms build up more cash reserves from cash flows, cut back payouts and raise more debt to maintain cash holdings.
Keywords: Bank lending; executive compensation; managerial incentives; investments; cash flows; cash holdings; Corporate Finance; Finance and Financial Management; Corporate Finance